Modernity, identity and utopia in Latin America - Quijano Obregón, Aníbal (2022)
Aníbal Quijano's text discusses the problem of modernity and its relations with Latin America. Quijano problematizes the Eurocentric debate centered on postmodernity since he considers it essential to keep the liberating promises of modernity. In Latin America, a "metamorphosis" of modernity takes place as it remains confined to subjectivity, blocking the possibilities of its implantation in the daily materiality of society. Finally, the text discusses the constitution in Latin America of an alternative rationality to the Eurocentric instrumental rationality. This new rationality is implied in the proposal of José María Arguedas. The Arguedian utopia carries a new historical sense where “the joy of collective solidarity and the individual fulfillment” are combined.